2018
DOI: 10.1016/j.cub.2018.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Traffic in the Late Steps of Cytokinesis

Abstract: Cells don't simply separate at cytokinesis. While furrow contraction critically relies on myosin-II and F-actin, post-furrowing steps are less understood but involve the constriction of ESCRT-III polymer-dependent helices on the side of the midbody, which likely drive final abscission. The first evidence that animal cell cytokinesis requires membrane traffic, as in plant cells, was provided about 15 years ago. Since then, it has become increasingly clear that fusion of vesicles to the cytokinetic furrow is ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
108
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 144 publications
(261 reference statements)
4
108
0
Order By: Relevance
“…C ytokinesis leads to the physical separation of daughter cells and concludes cell division. Final abscission occurs close to the midbody (or Flemming body), a prominent structure that matures at the center of the intercellular bridge connecting the two daughter cells and first described by Walther Flemming in 1891 [1][2][3][4][5][6][7][8][9] . The scission occurs not at the midbody itself, but at the abscission site located at distance on one side of the midbody [10][11][12][13][14] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C ytokinesis leads to the physical separation of daughter cells and concludes cell division. Final abscission occurs close to the midbody (or Flemming body), a prominent structure that matures at the center of the intercellular bridge connecting the two daughter cells and first described by Walther Flemming in 1891 [1][2][3][4][5][6][7][8][9] . The scission occurs not at the midbody itself, but at the abscission site located at distance on one side of the midbody [10][11][12][13][14] .…”
mentioning
confidence: 99%
“…Remarkably, ESCRT-III-dependent helices of 17 nm filaments are observed at the abscission site by electron microscopy (EM), and ESCRT-III helical structures are often visible extending from the midbody to the abscission site 10,36 . Therefore, as in other topologically equivalent ESCRT-III-mediated events, including exosome biogenesis in multivesicular bodies (MVBs), retroviral budding or membrane repair, constriction of ESCRT-III filaments likely drives the final membrane scission during cytokinetic abscission [2][3][4][5][6][7]9 .…”
mentioning
confidence: 99%
“…Abscission is the last step of mitotic cell division that leads to resolution of the intracellular bridge (ICB) and physical separation of two daughter cells. It is now becoming clear that abscission is a very complex and highly regulated event (Addi et al, 2018;Fremont and Echard 2018;Schiel and Prekeris 2010). Indeed, recent studies identified a new mitotic checkpoint, known as abscission checkpoint (also sometimes referred to as NoCut), that is activated by lagging chromosomes and leads to the arrest of the cells in telophase (Bai et al, 2020;Petsalaki and Zachos 2020;Sadler et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We now know that abscission involves highly organized remodelling of the cytoskeleton at the ICB. Specifically, the abscission site is defined by localized disassembly of actin cytoskeleton that is presumably a remnant of the cytokinetic contractile ring (Addi et al, 2018;Fremont and Echard 2018;Schiel et al, 2012). Actin depolymerisation then leads to spastin-dependent microtubule severing and formation of ESCRT polymers that eventually drives plasma membrane fusion and resolution of the ICB .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation